Two-photon coupling via Josephson element: Breaking the symmetry with magnetic fields - Stolyarov, Eugene; Andriichuk, Volodymyr; Sokolov, Andrii (Physical Review B, 2025)
We consider a coupling element based on a symmetric superconducting quantum interference device (SQUID) and show that it mediates a two-photon interaction. This and other inductive interactions due to the SQUID can be switched off in situ. We derive the system Hamiltonian for a coupled resonator and rf SQUID. The rf SQUID dwells in the vicinity of its metastable well holding a number of energy states and acts as an artificial atom. We discuss how the Josephson symmetry breaks owing to magnetic fields in the superconducting loops—both directly and via a nonzero superconducting phase difference over the rf SQUID. We assess that the two-photon coupling strength reaches 18 MHz which can exceed the single-photon capacitive interaction in the coupler.